190 Determinants of Psychological Well-Being in Healthcare Workers During the Covid-19 Pandemic: A Multinational Cross-Sectional Study. (4th May 2021) - Goh, E T; Denning, M; Purkayastha, S; Kinross, J
Abstract: Introduction: The Covid-19 pandemic has placed unprecedented pressures on healthcare systems globally, impacting working conditions, safety attitudes and the psychological well-being of healthcare workers. This cross-sectional study explores the prevalence and predictors of anxiety/depression amongst healthcare workers in the UK, Singapore, and Poland. Method: From 22 March to 18 June 2020, healthcare workers from the UK, Singapore and Poland were invited to complete a self-administered questionnaire on psychological well-being. Anxiety and depression were measured using the Hospital Anxiety and Depression Scale (HADS). Other components of the questionnaire include demographic information, Safety Attitudes Questionnaire (SAQ) measuring safety culture and the Oldenburg Burnout Inventory (OLBI) to measure burnout. Multivariate logistic regression was used to determine predictors of anxiety and depression. Results: Of 3537 healthcare workers who participated in the study, 701 (20%) screened positive for anxiety and 389 (11%) for depression. Significant predictors of depression and anxiety include low SAQ score, nursing role, redeployment, burnout, and depression. There was significant overlap between anxiety and depression. The doctor role was protective. Conclusions: Our findings demonstrate a significant burden of anxiety and depression amongst healthcare workers during Covid-19. These findings highlight the impact of Covid-19 on psychological well-being and suggests which groups would benefit from targeted support.